U.C. Berkeley's Camp Gold at the Lair - Watkins, Howard::::::::: (1986)
Howard Watkins, Jennifer Greene, Adam Watkins, Robin Watkins and Christine Watkins Howard's shirt reads "COGITO ERGO SUM COGITO"